On the Hermite-Hadamard Inequality and Other Integral Inequalities Involving Two Functions. (24th May 2010) - Set, Erhan; Özdemir, M. Emin; Dragomir, Sever S.
Abstract : We establish some new Hermite-Hadamard-type inequalities involving product of two functions. Other integral inequalities for two functions are obtained as well. The analysis used in the proofs is fairly elementary and based on the use of the Minkowski, Hölder, and Young inequalities.